Cytogenetic Investigation in Couples with Recurrent Abortion and Poor Obstetric History - Ebru Önalan Etem; Hüseyin Yüce; Deniz Erol; Şükriye Derya Deveci; Hüsnü Çelik; Halit Elyas (Medical Network, 2010)
OBJECTIVES: The cause of recurrent early pregnancy wastage is often unknown. Cytogenetic studies have an important role in the evaluation of couples with repeated miscarriages and poor obstetric history. STUDY DESIGN: To estimate the prevalence of chromosomal abnormalities and polymorphic variants, we performed G-banded chromosome analysis on 470 couples with 2 or more spontaneous abortions or bad obstetric history, the east of Turkey from 1998 to 2008. RESULTS: Major chromosomal aberrations and polymorphic variants were found in 2.12% and 2.34%, respectively. Complex chromosomal rearragements it was detected in one female patient. CONCLUSION: Our study suggest that chromosomal abnormality incidence in patients with fetal deaths/abnormality is much higher than in the patients with first trimester or second trimester recurrent abortion. Prenatal diagnosis should be offered to couples wiht balanced chromosomal carrier and in vitro fertilization to couples with complex chromosomal rearragements in the case of future pregnancies.